Emerging natural hybrid between Invasive Species and Native Congener of Emilia (Asteraceae) Found in Northern Taiwan - Wang, Jen-Yu; Wang, Jenn-Che (Phytotaxa, 2018)
Invasive plants had raised lots of concern about the environment and biodiversity. Many members of Asteraceae are notorious invasive alien species across the world. In Taiwan, Emilia (Asteraceae) contains one native and two naturalized species. Recently, we found some morphologically intermediate individuals between the native E. sonchifolia var. javanica and the alien E. praetermissa from northern Taiwan where the latter two grow sympatrically. Based on morphological comparisons, pollen viability and flow cytometry information, we confirmed the fact of natural hybridization. Herein, we describe a new hybrid Emilia ×latens J.-Y Wang & J.-C. Wang and provide a key to Emilia species in Taiwan.